A tool for global and regional Landsat 7 and Landsat 8 cross-sensor harmonization - Galen Richardson; Anders Knudby; Koreen Millard; Wenjun Chen (Geocarto International, 2025)
The Landsat archive can be used to track long-term landscape and environmental changes. However, substantial differences in atmospheric correction algorithms, radiometric resolution, and spectral response functions suggest that harmonization models should be implemented when using data from OLI/OLI-2 sensors with TM/ETM+ data. Harmonized data allows models to be applied across most of the Landsat archive, as biases caused by differences in sensor spectral response function and atmospheric correction algorithms have been minimized. We propose the Landsat ETM+ OLI Harmonization Script (LEOHS), a Python package using Google Earth Engine to facilitate region-specific harmonization between ETM+ and OLI data. Regional harmonization functions generated by LEOHS performed similarly or outperformed existing models in the same areas of interest. This study represents a significant advancement in sensor harmonization, and the LEOHS tool enables users to conduct more accurate and unbiased time series analyses with the Landsat archive.